2014
DOI: 10.1186/1471-2164-15-334
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Botrytis cinerea in Solanum lycopersicoides involves widespread transcriptional reprogramming

Abstract: BackgroundTomato (Solanum lycopersicum), one of the world’s most important vegetable crops, is highly susceptible to necrotrophic fungal pathogens such as Botrytis cinerea and Alternaria solani. Improving resistance through conventional breeding has been hampered by a shortage of resistant germplasm and difficulties in introgressing resistance into elite germplasm without linkage drag. The goal of this study was to explore natural variation among wild Solanum species to identify new sources of resistance to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 107 publications
5
46
1
Order By: Relevance
“…Previously, Smith et al (2014) identified Bcsun1 as one of the genes induced in planta during infection of Solanum lycopersicoides leaves. Altogether, these results suggested a role of BcSUN1 in fungal pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Smith et al (2014) identified Bcsun1 as one of the genes induced in planta during infection of Solanum lycopersicoides leaves. Altogether, these results suggested a role of BcSUN1 in fungal pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies focusing on the transcriptional regulation of responses to multiple stresses have identified commonly regulated genes responsive to both B. cinerea infection and simultaneous abiotic stresses, such as drought, heat, or salinity, in Arabidopsis using microarray analyses (Atkinson and Urwin, 2012; Sham et al, 2015). In tomato, a transcriptomic study using RNAseq has distinguished the natural variation among wild Solanum species (Smith et al, 2014). Following B. cinerea infection, photosynthetic and metabolic processes were suppressed, whereas defense-related genes, such as those encoding PR protein 1 (PR1), β-1,3-glucanase and subtilisin-like protease, were simultaneously induced in the highly B. cinerea -resistant species, S. lycopersicoides .…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Advances in high-throughput DNA sequencing, RNA sequencing (RNAseq), mass spectrometry (MS), and nuclear magnetic resonance (NMR) at the genomic, transcriptomic, proteomic and metabolomic levels, and through the multi-omics (also known as integrated-omics) (Shiratake and Suzuki, 2016), have made possible the development of such data into a systems biology-based framework ( Figure 1 ). High-throughput-next generation sequencing (HT-NGS) technologies, ranging from RNAseq to whole-genome sequencing, are fast, sensitive and accurate tools for detection of B. cinerea genome from symptomatic or asymptomatic plants and understanding defense mechanisms associated with fungal infections in planta (Smith et al, 2014). Moreover, HT-NGS techniques have promising applications at the molecular plant- B. cinerea interaction research.…”
Section: Introductionmentioning
confidence: 99%
“…Several quantitative trait loci conferring resistance or susceptibility to B. cinerea have been identified and mapped in tomato (Finkers et al, 2007; Davis et al, 2009). Significant transcriptional reprogramming, metabolic and biochemical changes, and modification of signal pathways operated by different stress hormones such as ethylene (ET), salicylic acid (SA), jasmonic acid (JA), and abscisic acid (ABA) are involved in the response of tomato or its wild species to B. cinerea (Blanco-Ulate et al, 2013; Seifi et al, 2014; Smith et al, 2014; Camañes et al, 2015; Vega et al, 2015). During the infection process, B. cinerea can manipulate the antagonistic balance between the SA- and JA/ET-mediated signaling pathways and hijack the SA signaling pathway to accelerate disease development (El Oirdi et al, 2011; Rahman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%